The Impact of Duty Hours Restrictions on Job Burnout in Internal Medicine Residents. (April 2015) - Ripp, Jonathan A.; Bellini, Lisa; Fallar, Robert; Bazari, Hasan; Katz, Joel T.; Korenstein, Deborah
<x xml:space="preserve">Abstract</x> Purpose Internal medicine (IM) residents commonly develop job burnout, which may lead to poor academic performance, depression, and medical errors. The extent to which duty hours restrictions (DHRs) can mitigate job burnout remains uncertain. The July 2011 DHRs created an opportunity to measure the impact of decreased work hours on developing burnout in IM residents. Method A survey was administered twice to first-year IM residents at three academic medical centers between June 2011 and July 2012. To estimate the impact of the 2011 DHRs, data from this cohort, including demographics, sleepiness, hospital-based patient service characteristics, and burnout measures, were compared with data from 2008–2009 from first-year IM residents at the same institutions. Results Of eligible residents, 128/188 (68%) from the 2011–2012 cohort and 111/180 (62%) from the 2008–2009 cohort completed both surveys. Year-end burnout prevalence (92/123 [75%] versus 91/108 [84%], P = .08) and incidence (59/87 [68%] versus 55/68 [81%], P = .07) did not differ significantly between cohorts. There was no difference in year-end prevalence of excessive Epworth sleepiness (72/122 [59%] versus 71/108 [66%], P = .29) between cohorts; however, a greater percentage of residents who developed burnout in the 2011–2012 cohort reported caring for > 8 patients on their service (2011–2012 versus 2008–2009) (29/59 [49%] versus 5/34 [15%], P < .01). Conclusions Job burnout and self-reported sleepiness in IM resident physicians were unchanged after the 2011 DHRs at three academic institutions. Further investigation into the determinants of burnout can inform effective interventions.